Suyûtî'ye nispet edilen er-Rahme fıt-Tıbb vel-Hikme'deki hadislerin tahric ve değerlendirmesi - RASOOL, JAWAD TAHA (Fırat Üniveristesi, 2022)
İtikadî, teşri ve özellikle tıbbî açıdan hayatın tüm alanlarında büyük bir tahribata yol açan zayıf ve uydurma hadisler, Müslümanlar arasında yayılmıştır. Allahu Tealâ, hadis imamlarını, sahih hadisleri zayıf ve illetli hadislerden beyan etmekle onları görevlendirmiştir. Bu çalışma, Suyûtî'ye nispet edilen "er-Rahme fıt-Tıbb vel-Hikme"'de yer alan yirmi sekiz adet hadis ihtiva etmektedir. Tahricini yaptığım bu hadislerden sekiz'i sahih, beş'i zayıf, on beş'i uydurmadır. Çalışmamı dört bölümden oluşturdum. Birinci böl?mde Celâlüddîn es-Suyûtî'nin hayatını ve çok kısa bir şekilde ona nispet edilen "er-Rahme fıt-Tıbb vel-Hikme"'yi, ikinci bölümde sahih, zayıf ve uydurma olmak üzere mezkûr kitapta yer alan hadislerin tahricini, üçüncü bölümde hadislerde geçen bitkiler, bal, süt ve hurma gibi ilaçların adını, dördüncü bölümde de hacamat, dağlamak, sürme çekmek ve bunların faydalarını ele aldım.

Indeed, weak Hadiths have been spread among Muslims which they may lead to misguidance in their religious creed, legitimacy and treatments. Allah almighty, demands the scholars to clarify and differentiate the Sahih Hadiths from the weak and fabricated ones. Allah almighty, granted me with a blessing to allot this work to the prophetic Hadiths (Peace be upon him) to differentiate the Sahih Hadiths from the weak and fabricated ones. My study consists of 28 Hadiths; which I have extracted them from the book (Ar-rahma fi-l tub walhikma). It's mistakenly narrated in the name of Jalal al-din al-siuty. Eight of the Hadiths are sahih. Five of them are weak, and the other 15 are fabricated. My work consists of four chapters. The first chapter is about the biography of Jalal al-din al-siuty, a brief introduction to the book (Ar-rahma fi-l tub wal-hikma), and how it's mistakenly narrated in the name of Al-Siuty. The second chapter is about the extraction of the Hadiths. It's divided into three sections: the sahih Hadiths, the weak Hadiths, and the fabricated Hadiths. In the third chapter, those treatments which are mentioned in the Hadiths, are discussed about; such as treatment with herbs, honey, milk, and dates.In chapter four, other treatments like cupping and kohl are discussed.
The extraction and studying the prophetic hadiths in the book (ar-Rahma fi-l Tub wal-Hikma) belongs to Siuty
Keywords: Din